Molecular Characterisation of Upland and Lowland Rice from Sarawak, Malaysian Borneo - Freddy Kuok San, Yeo; Renee Priscilla Trawas, Sylvester Embuas; ZAZEVIA FRANK, CLIFTON; Meekiong, Kalu; Zinnirah, Shabdin; Lee San, Lai (UNIMAS Publisher, 2025)
A total of 39 Simple Sequence Repeat (SSR) markers distributed across 12 chromosomes were screened to assess genetic polymorphism among rice accessions. From the 39 tested SSR primer pairs, eight markers (RM1, RM489, RM552, RM444, RM257, RM481, RM166 and RM164) exhibited clear polymorphic banding patterns and strong amplification, while the remaining were excluded due to monomorphism or unclear bands. Among the selected primers, RM257 recorded the highest polymorphic information content (PIC) value (0.9316), while RM552 had the lowest (0.4029), with an average PIC of 0.6891. The observed number of effective alleles (Ne) was 1.543 in the lowland population and 1.566 in the upland population. Nei’s gene diversity (h) was 0.329 for lowland and 0.318 for upland populations, suggesting a low level of genetic divergence. Similarly, Shannon’s Information Index (I) values were 0.475 and 0.490 for lowland and upland populations, respectively. Analysis of Molecular Variance (AMOVA) revealed that 20% of genetic variation existed among populations, while 80% occurred within populations. Clustering analysis using a UPGMA dendrogram based on SSR genotypes grouped the 44 rice accessions into two major clusters, each further divided into sub-clusters. However, no clear grouping was observed based on morphological traits or geographical origin, likely due to the higher sensitivity of molecular markers in detecting underlying genetic differences that are not always reflected in visible traits. Unlike conventional morphological classification which relies on observable characteristics such as grain shape, plant height or habitat, genome-based clustering captures deeper genetic relationships that offer a more accurate picture of population structure. Simultaneously, the Maturase-K barcoding gene marker grouped the accessions into a single large cluster, which also included 94 accessions from diverse origins and three accessions of Oryza rufipogon, indicating genome-level similarities. These findings underscore the utility of molecular markers in revealing genetic diversity and population structure. The insights gained from this study can support the development of targeted rice breeding programs essential for advancing sustainable agriculture.